Changes in Water Sorption and Solubility of Dental Adhesive Systems after Cigarette Smoke. (28th July 2013) - Vitória, Lívia Andrade; Aguiar, Thaiane Rodrigues; Santos, Poliana Ramos Braga; Cavalcanti, Andrea Nóbrega; Mathias, Paula
Abstract : Aim . To evaluate the effect of cigarette smoke on water sorption and solubility of four adhesive systems. Materials and Methods . Sixteen disks of each adhesive system were prepared (Adper Scotchbond Multipurpose Adhesive (SA); Adper Scotchbond Multipurpose Adhesive System (Adhesive + Primer) (SAP); Adper Single Bond Plus (SB); Adper Easy One (EO)). Specimens were desiccated until a constant mass was obtained and divided into two groups ( n = 8 ) . One-half of the specimens were immersed in deionized water, while the other half were also immersed, but with daily exposure to tobacco smoke. After 21 days, disks were measured again and stored in desiccators until constant mass was achieved. Data were calculated according to ISO specifications and statistically analyzed. Results . The tobacco smoke only significantly affected the water sorption and solubility of EO. There were significant differences in both analyses among materials tested. The SB exhibited the highest water sorption, followed by EO, which demonstrated significantly higher solubility values than SB. The SA and SAP showed low water sorption and solubility, and there were no significant differences between the two. Conclusion . Regardless of smoke exposure, both simplified adhesive systems presented an inferior performance that could be related to the complex mixture of components in such versions.